(untitled) (Perner’s Contacts, 2011)
The paper deals with the analysis of factors affecting the realisation of SWOT analysis related to the location of new warehouses in the Slovak Republic. These are major factors that determine the selecting of a suitable location for the purpose of warehouses optimal placing. By performing of this analysis it can be contributed to easier decision-making about the construction of modern storage facilities by different developers.